PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR INDUSTRI BARANG KONSUMSI TAHUN 2015-2019 - Astriyah, Deni; Simamora, Saur Costanius (JURNAL ILMIAH M-PROGRESS, 2022)
This study aims to determine the effect of institutional ownership and Corporate Social Responsibility on firm value, where company value is measured using Tobin's Q. The population in this study is the consumer goods industry sector companies listed on the IDX for the 2015-2019 period, amounting to 61 companies. The method of determining the sample using purposive sampling, so that the sample in this study were 19 companies. This study uses secondary data in the form of financial reports obtained from www.idx.co.id and the official websites of each company             The data analysis method is multiple linear regression, with partial and simultaneous hypothesis testing. The results of this study indicate that institutional ownership and Corporate Social Responsibility have a significant effect on firm value. In addition, in this study, institutional ownership and Corporate Social Responsibility had an effect of 50.4%, while the remaining 49.6% was influenced by other variables that were not in the linear regression model in this study. Keywords: Institutional Ownership, Corporate Social Responsibility, Company Value